The Role of Genetic Data in Selecting Device-Aided Therapies in Patients With Advanced Parkinson’s Disease: A Mini-Review - Chan, Germaine Hiu-Fai (Frontiers in Aging Neuroscience, 2022)
Parkinson’s disease (PD) is a common neurodegenerative disease. At present, 5 – 10% of PD patients are found to have monogenic form of the disease. Each genetic mutation has its own unique clinical features and disease trajectory. It is unclear if the genetic background can affect the outcome of device-aided therapies in these patients. In general, monogenic PD patients have satisfactory motor outcome after receiving invasive therapies. However, their long-term outcome can vary with their genetic mutations. It appears that patients with LRRK2 and PRKN mutations tended to have good outcome following deep brain stimulation (DBS) surgery. However, those with GBA mutation were found to have poorer cognitive performance, especially after undergoing subthalamic nucleus (STN) DBS surgery. In this review, we will provide an overview of the outcomes of device-aided therapies in PD patients with different genetic mutations.